1 & 2 Samuel - Gordon, R. P. (Old Testament guides., 1987)
A comprehensive introduction to the critical issues raised by scholarship on both books of Samuel. The often intricate problems are dealt with clearly and engagingly; the chapters deal with the Deuteronomistic History, the Shiloh tradition, the Ark narrative, the rise of the monarchy, the reign of Saul, the story of David, the Davidic covenant, the Succession Narrative and the Samuel appendix. A first-rate guide for students, with annotated bibliographies and indexes.